Convalescent plasma for COVID-19: a meta-analysis, trial sequential analysis, and meta-regression. (December 2021) - Snow, Timothy A.C.; Saleem, Naveed; Ambler, Gareth; Nastouli, Eleni; McCoy, Laura E.; Singer, Mervyn; Arulkumaran, Nishkantha
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific antibodies, particularly those preventing interaction between the viral spike receptor-binding domain and the host angiotensin-converting enzyme 2 receptor, may prevent viral entry into host cells and disease progression. Methods: We performed a systematic review, meta-analysis, trial sequential analysis (TSA), and meta-regression of RCTs to evaluate the benefit of convalescent plasma for COVID-19. The primary outcome was 28–30 day mortality. Secondary outcomes included need for mechanical ventilation and ICU admission. Data sources were PubMed, Embase, MedRxiv, and the Cochrane library on July 2, 2021. Results: We identified 17 RCTs that recruited 15 587 patients with 8027 (51.5%) allocated to receive convalescent plasma. Convalescent plasma use was not associated with a mortality benefit (24.7% vs 25.5%; odds ratio [OR]=0.94 [0.85–1.04]; P =0.23; I 2 =4%; TSA adjusted confidence interval [CI], 0.84–1.05), or reduction in need for mechanical ventilation (15.7% vs 15.4%; OR=1.01 [0.92–1.11]; P =0.82; I 2 =0%; TSA adjusted CI, 0.91–1.13), or ICU admission (22.4% vs 16.7%; OR=0.80 [0.21–3.09]; P =0.75; I 2 =63%; TSA adjusted CI, 0.0–196.05). Meta-regression did not reveal association with titre of convalescent plasma, timing of administration, or risk of death and treatment effect ( P >0.05). Risk of bias was high in most studies. Conclusions: In patients with COVID-19, there was no clear mortality benefit associated with convalescent plasma treatment. In patients with mild disease, convalescent plasma did not prevent either the need for mechanical ventilation or ICU admission. Clinical trial registration: CRD42021234201 (PROSPERO).